Vibration Analysis of a Carbon Nanotube Reinforced Uniform and Tapered Composite Beams - BABU ARUMUGAM, Ananda; RAJAMOHAN, Vasudevan; BANDARU, Naresh; SUDHAGAR P., Edwin; G. KUMBHAR, Surajkumar (Archives of Acoustics, 2019)
In this study, free and forced vibration responses of carbon nanotube reinforced uniform and tapered composite beams are investigated. The governing differential equations of motion of a carbon nanotube (CNT) reinforced uniform and tapered composite beams are presented in finite element formulation. The validity of the developed formulation is demonstrated by comparing the natural frequencies evaluated using present FEM with those of available in literature. Various parametric studies are also performed to investigate the effect of aspect ratio, percentage of CNT content, ply orientation, and boundary conditions on natural frequencies and mode shapes of a CNT reinforced composite beam. It was observed that the addition of carbon nanotube in fiber reinforced polymer composite (FRP) beam enhance the stiffness of the structure which consequently increase the natural frequencies and alter the mode shapes.